LITERASI PENDIDIKAN BELA NEGARA DI KAMPUNG SELAAWI DESA CIBALUNG KECAMATAN CIJERUK - Dida Nursida; Muhammad Adriyankan; Siti Halimatu Sa'diyah (Institut Madani Nusantara, 2023)
State defense is the service of all citizens in all its forms, for the benefit of the nation and state, which refers to its condition as the Dharma of Religion and the Dharma of the State. This defensive attitude will help strengthen the condition of this great nation called Indonesia to survive in the midst of such a rapid global progress that covers all dimensions of human life, especially in Cibalung village, Cijeruk sub-district. Indonesia will continue to live in diversity, progress in realizing the ideals of independence, and be strong in the eyes of the world. This will be strengthened and strengthened by our Pancasila values as views and guidelines for living with a personality, community, nation and state.